Pengaruh Komitmen dan Iklim Organisasi terhadap Kinerja Guru - Siti Wahyuni; Dyah Sawitri; Moch. Saleh (Jurnal Mirai Management, 2022)
The researcher’s intention of doing this research is to reveal The Effect of Commitment and Organizational Climate on Teachers’ Performance at Bina Bangsa Wilmar-CKP private elementary school. The purpose of this research is to determine the effect of commitment and organizational climate simultaneously, partially, and to determine the biggest influence between the two on teachers’ performance at Bina Bangsa Wilmar-CKP private elementary school. This research uses qualitative approach with the combination of descriptive and explanatory research types. The populations of this research are three schools of Bina Bangsa private elementary school, which are under Bina bangsa Wilmar-CKP educational foundation, using error rate of 5%. This research uses the Bina Bangsa Private Elementary School Teacher respondent questionnaire method as a data collection technique and documentation method to obtain secondary information needed. In this research validation test is conducted using product moment model Pearson’s correlation approach, while instrument reliability test is conducted using Alpha Cronbach. Hypothesis testing in this research uses multiple linier regression techniques with F Test and t Test. Keywords: keyword_ Commitment, Organizational Climate, Teacher Performance